Are there two types of business cycles? A note on crisis detection - Robert Pater (e-Finanse: Financial Internet Quarterly, 2014)
Business cycles are highly irregular fluctuations in economic activity. This article attempts to determine whether there are some properties of business cycles that can make them look more regular. This is done by analysing business cycle dynamics, especially by employing and adjusting to contemporary business cycle analysis the theories of growth cycles and classical cycles. The non-homogeneity of business cycles is surveyed in theory and practice with use of ad hoc filtering, spectral analysis and unobserved components models. With their use business cycles are extracted. Several macroeconomic indicators for 32 economies are analysed to draw up additional characteristics of contemporary business cycles. The author proposes that fluctuations in economic activity lasting 8-19 quarters should be called "growth cycles" and those lasting 20-40 quarters - "classical cycles". The value added of this article is the consideration of the two different type of cycles in light of the same methods of extraction, while to date they have been thought of as the ones that can be analysed with use of different methods of extraction. Another innovation is comparison of the cyclicality of different macroeconomic indicators from the point of view of the two types of cycles, while to date they have been analysed in the light of a single business cycle. In the article it is shown that dividing business cycles into such defined classical cycles and growth cycles enables us to understand the differences between the cyclicality of various macroeconomic aggregates and countries. It also enables us to distinguish between smaller downturns and severe recessions. Another conclusion is that the duration of contemporary business cycles around the world closes in a range of 2 to 10 years.
Keywords: E32; E37; 330; business cycle; growth cycle; classical cycle; unobserved components